No Structure without Culture? A Survey Study of 15–19 Year Olds' Practices, Preferences and Perceptions of Physical Activity in a Danish Upper Secondary School. (November 2018) - Nielsen, Stine Frydendal; Nielsen, Glen; Ottesen, Laila Susanne; Thing, Lone Friis
This article presents the results of a questionnaire survey conducted in a Danish upper secondary school where alternative options of physical activity have been provided to the students. The purpose of the study is to gain knowledge about the perspectives of the students concerning physical education (PE), sport and exercise. The study illustrates young people's practices, preferences and perceptions when physical activity is a gender-integrated activity as is the case in Denmark. The results are discussed in a figurational perspective viewing PE, sport and exercise as interdependent dimensions influencing young people's participation in and views on physical activity. The study shows that even though we have a long tradition of gender-integrated PE in Denmark, very traditional gender differences similar to countries with gender-segregated PE prevails. The article, therefore, discusses the significance of cultural rather than structural circumstances while studying practices, preferences and perceptions of physical activity among young people.